Pencegahan Perbuatan Bullying di Kalangan Siswa SMP Negeri 21 Kabupaten Tanjung Jabung Timur - Helmi Helmi; Hafrida Hafrida; Dessy Rakhmawati; Aga Anum Payudhi (CV. Ulil Albab Corp, 2023)
The aim of this service is to prevent bullying from occurring. Bullying is common among teenagers. Bullying is any form of oppression or violent acts carried out intentionally by one person or a group of people with the aim of hurting and carried out continuously. Sometimes the perpetrator of bullying is not aware that his actions constitute bullying. There are several types of bullying, physical bullying and verbal bullying, physical bullying can be recognized by the presence of wounds or bruises, but verbal bullying is difficult to identify, verbal bullying such as mocking, insulting, giving negative nicknames, making fun of etc. . From data obtained from the Child Protection Commission, bullying is increasing every year. The impact of this act of bullying is very dangerous. Victims of bullying can become insecure, feel inferior, get emotional easily and can even have the intention to commit suicide. For this reason, through the implementation of this service, it is hoped that bullying can be prevented among students at SMP Negeri 21, East Tanjung Jabung Regency.